Discourse of Difference: Rosa Campbell Praed’s My Australian Girlhood - Klepač, Tihana (2011)
Australian nationalist metanarrative performed “cultural apartheid” (Summers) over female literary production. Excluded from official discourse and the dominant literary genres, women resorted to those available in the attempt to formulate their subjectivity. Hence their narratives became a means of talking back. Consequently, Rosa Campbell Praed’s My Australian Girlhood (1902) demonstrates characteristics of autobiography, travel literature and adventure narrative, and at the same time transgresses the said genres in both, their intent, as well as their structural characteristics. Additionally, travelling within the colonial context, Praed inevitably participates in the discourses of imperialism, which she is, however, found rupturing as she criticises British racial policy in Australia, thus revealing her writing as double-voiced. As a female colonial writer, writing within a masculine realist literary tradition, Praed was othered by contemporary critics who either devalued her writing, or altogether dismissed it as un-Australian, ignoring numerous instances wherein she contributes to the formulation of the national identity as formulated in the 1890s. Therefore to read Praed’s text means to be aware of the historically and culturally specific context.
Projekt MZOS
ENG